Digitizing Trust: Ethical Dimensions of InsurTech in the Era of Financial Inclusion - Gurucharann Visagamurthy (Journal of Computer Science and Technology Studies, 2025)
Insurance technology (InsurTech) signifies a transformative reconfiguration of how financial protection services are delivered and accessed, particularly for historically underserved populations. The digitalization of insurance operations extends beyond improvements in efficiency, fundamentally altering access dynamics for rural communities, older adults, and digitally excluded individuals. Innovations such as automated enrollment systems, real-time underwriting algorithms, and interoperable data platforms hold considerable promise for advancing financial inclusion. However, these advancements also raise pressing ethical concerns related to data privacy, algorithmic accountability, and equitable service provision. Addressing these challenges requires robust governance frameworks, inclusive regulatory policies, and active stakeholder engagement. Key enablers, such as digital literacy programs, bias mitigation strategies, and human-centered design, are essential to ensuring that technological innovation aligns with broader societal objectives. The continued evolution of insurance ecosystems hinges on the ability to reconcile the pursuit of operational scale and efficiency with the core principles of fairness, transparency, and public trust.